THE ARRANGEMENT OF CHILD PROTECTION INSTITUTIONS IN INDONESIA BASED ON THE 1945 INDONESIAN CONSTITUTION - Fauzan, Encik Muhammad; Arifta, Ariyanti (Faculty of Law Universitas Trunojoyo Madura, 2020)
Children have constitutional rights as stipulated in the 1945 Indonesian Constitution. The implementation of children's rights requires the formation of institutions that protect children's rights in accordance with the 1945 Indonesian Constitution and how the existence of child protection institutions that have been in Indonesia today. The research aims to provide the basis for the establishment of child protection institutions and the arrangement of child protection institutions in Indonesia. This research method uses normative research with a statute approach. The results of this study indicate that the implementation of child protection requires special institutions. The existence of two child protection institutions, namely The Indonesian Children Protection Commission (ICPC) and a National Commission for Children Protection (NCCP), require institutional arrangements so that authority does not overlap.